NILAI-NILAI DASAR DAKWAH ISLAM BERBASIS KEARIFAN SOSIAL DALAM LITERATUR DAKWAH NUSANTARA - Muhammad Sayyed Ja’far Bolkia; Sarbini Anim; Siti Nuri Nurhaidah (LPPM STAI Muhammadiyah Probolinggo, 2026)
This research departs from the urgency of responding to the weakening of contextual da’wah values amidst waves of globalization and religious polarization that threaten the social harmony of Indonesian society. Da’wah that is uprooted from local wisdom tends to produce exclusive and conflictual religious practices. The purpose of this study is to identify, analyze, and deconstruct the basic values of Islamic da’wah based on social wisdom as recorded in Nusantara da’wah literature, as well as to examine their relevance for contemporary life. This research employs a qualitative approach using the library research method. Primary data sources were obtained from classical and contemporary Nusantara da’wah literary works, while secondary sources include relevant journal articles, books, and research reports from the last seven years. Data collection was carried out through systematic documentation, while data analysis employed content analysis and hermeneutic analysis to interpret the meaning of texts in their socio-historical context. The findings reveal that Nusantara da’wah literature contains foundational Islamic da’wah values that consistently integrate the principles of tawhid, noble character, Islamic brotherhood, and enjoining good and forbidding evil with local social wisdom such as mutual cooperation, deliberation, inter-religious tolerance, and social solidarity. Nusantara scholars and preachers, through their works, have built an inclusive da’wah model that positions culture as a medium, rather than an obstacle, in the spread of Islam. These values are proven relevant for strengthening religious moderation, maintaining national harmony, and addressing the challenges of radicalism and digital disruption in the contemporary era. These findings affirm that Nusantara Islam is not merely a geographical term, but a robust intellectual and da’wah tradition grounded in social wisdom.